2012
DOI: 10.4081/ni.2012.e17
|View full text |Cite
|
Sign up to set email alerts
|

Status epilepticus in the elderly: epidemiology, clinical aspects and treatment

Abstract: The aim of the study was to review the epidemiology, clinical profile and discuss the etiology, prognosis and treatment options in patients aged 60 years or older presenting with status epilepticus. We performed a systematic review involving studies published from 1996 to 2010, in Medline/PubMed, Scientific Electronic Library on line (Scielo), Latin-American and Caribbean Center of Health Sciences Information (Lilacs) databases and textbooks. Related articles published before 1996, when relevant for discussing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 59 publications
1
20
1
2
Order By: Relevance
“…SE incidences and mortality rate increased slightly over this period ( Table 1). The incidence rates in this study were lower than previous reports from the Western countries [4][5][6][7][8][9][10]. In 2012, the incidence rate of SE in the Thai elderly population was 8.78/100,000 population, while a study from California found an incidence rate there of 22.3/100,000 population in a generalized tonic clonic SE in the elderly aged 75 years and older [10].…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…SE incidences and mortality rate increased slightly over this period ( Table 1). The incidence rates in this study were lower than previous reports from the Western countries [4][5][6][7][8][9][10]. In 2012, the incidence rate of SE in the Thai elderly population was 8.78/100,000 population, while a study from California found an incidence rate there of 22.3/100,000 population in a generalized tonic clonic SE in the elderly aged 75 years and older [10].…”
Section: Discussioncontrasting
confidence: 83%
“…Several studies have shown that the incidences of SE in people over 60 were higher than in the general population [4][5][6][7]. The incidence rate of SE in the elderly (over 60 years old) was 39.2/100,000 population and higher than that in the younger age group (20-59 years) of 14.7/ 100,000 population [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher mortality rate, was found in those patients who presented SE, 78% (7 patients). The high mortality rate ascertained in our study is similar to that described by most authors and also shows a strong dependence on etiological factors and age 24,25 . The data from some studies showed that SE was associated with a mortality rate ranging from 38% to 50% in patients older than 80 years of age and it may reach 100% in patients with anoxia 26,27 .…”
Section: Discussionsupporting
confidence: 77%
“…It is the third most frequent neurological disorder in the elderly following stroke and dementia and even more relevant because, in this growing age group, it is often neglected 2 . In Brazil and in developed and some developing countries the demography profile is changing with increasing life expectation, thus the elderly comprise the fastest growing group of the population 3 . Currently 25 to 30% of new onset epilepsy is diagnosed in elders 4,5 .…”
mentioning
confidence: 99%